The use of amino acid analyses in (palaeo-) limnological investigations: A comparative study of four Indian lakes in different climate regimes. (1st July 2015) - Menzel, Philip; Anupama, Krishnamurthy; Basavaiah, Nathani; Das, Brijraj Krishna; Gaye, Birgit; Herrmann, Nicole; Prasad, Sushma
Abstract: In the present study, we report the results of comprehensive amino acid (AA) analyses of four Indian lakes from different climate regimes. We focus on the investigation of sediment cores retrieved from the lakes but data of modern sediment as well as vascular plant, soil, and suspended particulate matter samples from individual lakes are also presented. Commonly used degradation and organic matter source indices are tested for their applicability to the lake sediments, and we discuss potential reasons for possible limitations. A principal component analysis including the monomeric AA composition of organic matter of all analysed samples indicates that differences in organic matter sources and the environmental properties of the individual lakes are responsible for the major variability in monomeric AA distribution of the different samples. However, the PCA also gives a factor that most probably separates the samples according to their state of organic matter degradation. Using the factor loadings of the individual AA monomers, we calculate a lake sediment degradation index (LI) that might be applicable to other palaeo-lake investigations.